THE INFLUENCE OF FINANCIAL LITERACY AND SPENDING HABITS ON SHOPPING DECISIONS IN MARKETS WITH PERSONAL PREFERENCE AS A MODERATION VARIABLE - Arsy Maulana Firdaus; Sigit Hermawan (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the influence of financial literacy and spending habits on consumer decision-making among university students. Method: A quantitative approach was applied, involving a sample of 115 students from the Spring 2020 semester at the University of Sidoarjo. Data were analyzed using purposive sampling, validity and reliability testing, paired-probability hypothesis testing, and SPSS version 26 software. Results: The findings indicate that financial literacy has a positive and significant effect on consumer decision-making, whereas spending habits exert a negative effect. Novelty: The study highlights that financial literacy serves as a moderating factor in the relationship between financial behavior and decision-making, suggesting that sound financial management practices can enhance rational and informed consumer choices.